Peningkatan Aktivitas Belajar Siswa Melalui Model Snowball Throwing di Sekolah Dasar - SANTIKA, MIRA; Fahrudin, Farida; Aulia, Weni (Universitas Pahlawan Tuanku Tambusai, 2019)
This study was motivated by the low activity and student learning outcomes in science teaching class V SDN 28 Jorong Nan Tigo Pesisir Selatan District. The purpose of this study was to describe the increase in activity and learning outcomes fifth grade students of SDN 28 Jorong Nan Tigo Pesisir Selatan District, using the modelÂ Project Based Learning. This type of research is classroom action research (PTK). This study was conducted in two cycles. The data source is a fifth grade students of SDN 28 Jorong Nan Tigo Pesisir Selatan District amounted to 18 people. The instrument used is the observation sheet student activities, teacher observation sheet activities and achievement test. Based on the analysis of activities and student learning outcomes, student activity observation Score average first cycle of 58.32%, an increase in cycle II became 78.88% and student learning outcomes in the first cycle with an average of 61.11% completeness increased in the second cycle amounting to 78.05%. It can be said, learning science by using Project Based Learning model of increasing the activity and student learning outcomes. From the research, it is recommended that teachers can use the model of Project Based Learning in an effort to increase the activity and student learning outcomes in learning science. Â